2010
DOI: 10.2166/wst.2010.610
|View full text |Cite
|
Sign up to set email alerts
|

The effect of urban landfill leachate characteristics on the coexistence of anammox bacteria and heterotrophic denitrifiers

Abstract: Heterotrophic denitrification coexists with the anammox process contributing to N removal owing to the biodegradable organic matter supply from urban landfill leachate and the decay of microorganisms. Both biomasses consumed nitrite increasing the nitrite requirements of the system. The aim of this paper is the study of the causes which induce the system to decrease nitrogen removal efficiency. In this study, urban landfill leachate has been treated in an anammox Sequencing Batch Reactor (SBR) for 360 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
(8 reference statements)
1
21
0
Order By: Relevance
“…Ganigué et al [7] demonstrated the feasibility of this process for the long-term treatment of leachate with an extremely high ammonium concentration (up to 5000 mg N-NH 4 + L −1 ). The anammox process can thus be applied to treat urban landfill leachate that has been previously subjected to a partial nitritation process with a high level of removal efficiency [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ganigué et al [7] demonstrated the feasibility of this process for the long-term treatment of leachate with an extremely high ammonium concentration (up to 5000 mg N-NH 4 + L −1 ). The anammox process can thus be applied to treat urban landfill leachate that has been previously subjected to a partial nitritation process with a high level of removal efficiency [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have also demonstrated that a suitable influent NO 2 − N/NH 4 + N molar ratio is a crucial factor for avoiding problems in the anammox SBR performance during the treatment of urban landfill leachate. [35] This study also demonstrated that an excess of nitrite implied nitrite accumulation in the reactor and a lower nitrite supply than necessary for the system could force a loss of SAA due to nitrite competition with denitrifiers. [35] To summarize the results obtained with inoculum III, Figure 5 shows the variation of the nitrogen loading rate (NLR) and the nitrogen load in the effluent with time.…”
Section: Start-up and Operation Of The Sbrs Using Inocula III And Ivmentioning
confidence: 66%
“…[35] This study also demonstrated that an excess of nitrite implied nitrite accumulation in the reactor and a lower nitrite supply than necessary for the system could force a loss of SAA due to nitrite competition with denitrifiers. [35] To summarize the results obtained with inoculum III, Figure 5 shows the variation of the nitrogen loading rate (NLR) and the nitrogen load in the effluent with time. It can be seen that the effluent nitrogen load was kept virtually constant despite the increase in the NLR from 0.02 to 0.1 g N/L/d during the operating period.…”
Section: Start-up and Operation Of The Sbrs Using Inocula III And Ivmentioning
confidence: 66%
See 1 more Smart Citation
“…[28] The anammox process was studied and applied mainly for the treatment of the liquid fraction of municipal sludge digestate, of waste streams from the food industry (such as digested potato wastewater, and fish canning effluents) of leachate and recent study demonstrates the applicability also for waste-water in the mainstream. [29][30] In the …”
Section: Case 2 -Anammoxmentioning
confidence: 99%